From Courtrooms to Charts: The Impact of Kavanaugh's Appointment on Music Consumption - Luca Rossi; Michelangelo Rossi (Center for Economic Studies and ifo Institute (CESifo), 2024)
This study examines the impact of Brett Kavanaugh's Supreme Court appointment on U.S. music consumption, specifically exploring changes in streaming patterns on Spotify. With a difference-in-differences approach, we analyze the streaming data of the top 200 songs, revealing a significant increase of at least 13% in the streams of songs by female artists post-appointment. This sustained shift in consumer behaviour suggests a reaction to heightened media attention on gender issues. Our findings are robust against confounding factors such as seasonal trends and Spotify's promotional activities. Further, the study delves into the role of sexist lyrics, finding a more pronounced effect in songs with sexist terms. This research contributes to understanding political consumerism, showing how significant socio-political events can influence consumer preferences in seemingly unrelated sectors like the music industry. It underscores the importance of adaptive strategies in digital marketplaces in response to external socio-political changes, and highlights the broader societal implications of major events on consumer behaviour and attitudes, particularly concerning gender imbalances.
Keywords: J16; L82; 330; gender equality; music industry; social movements; political consumerism